Ophthalmic Artery Chemosurgery for Less Advanced Intraocular Retinoblastoma: Five Year Review - Abramson, David H.; Marr, Brian P.; Brodie, Scott E.; Dunkel, Ira; Palioura, Sotiria; Gobin, Y. Pierre (PLOS ONE, 2012)
Background Ophthalmic artery chemosurgery (OAC) for retinoblastoma was introduced by us 5 years ago for advanced intraocular retinoblastoma. Because the success was higher than with existing alternatives and systemic side effects limited we have now treated less advanced intraocular retinoblastoma (Reese-Ellsworth (RE) I-III and International Classification Retinoblastoma (ICRB) B and C). Methodology/Principal Findings Retrospective review of 5 year experience in eyes with Reese Ellsworth (Table 1) I (7 eyes), II (6 eyes) or III (6 eyes) and/or International Classification (Table 2) B (19 eyes) and C (11 eyes) treated with OAC (melphalan with or without topotecan) introduced directly into the ophthalmic artery. Patient survival was 100%. Ocular event-free survival was 100% for Reese-Ellsworth Groups I, II and III (and 96% for ICRB B and C) at a median of 16 months follow-up. One ICRB Group C (Reese-Ellsworth Vb) eye could not be treated on the second attempt for technical reasons and was therefore enucleated. No patient required a port and only one patient required transfusion of blood products. The electroretinogram (ERG) was unchanged or improved in 14/19 eyes. Conclusions/Significance Ophthalmic artery chemosurgery for retinoblastoma that was Reese-Ellsworth I, II and III (or International Classification B or C) was associated with high success (100% of treatable eyes were retained) and limited toxicity with results that equal or exceed conventional therapy with less toxicity.